Finnish landscape studies – a mixture of traditions and recent trends in the analysis of nature-human interactions - Niina Käyhkö; Olavi Granö; Maunu Häyrynen (Belgeo)
Finnish landscape studies have long methodological traditions stretching back to the early 20th century. These are reflected in present-day landscape research, which is practised within various university disciplines and research institutions, representing both the sciences and the humanities and also applied fields. We have categorised Finnish landscape studies under four main themes: (1) theoretical and methodological, (2) ecological, (3) social and cultural, and (4) applied. The focus of Finnish landscape research has been on both physical landscape characteristics and their spatial and temporal interactions, and also on the diverse social context of landscapes. Finnish landscapes have been mapped and delineated on several occasions, the latest landscape map being based on a publication by the National Land Survey and the Geographical Society of Finland dating from 1994. This classification recognizes landscape areas defined hierarchically on three spatial levels using the proportions and spatial configurations of ground, water, vegetation and man-made forms. The future of Finnish landscape studies is tied to whether knowledge about nature-human interactions on the visible surface of the earth will be able to overcome the fragmentation brought about by specialization. What is needed is a common world of concepts, a new way of thinking. This will call for transdisciplinary concepts, intertraditional points of view, in which quantitative and explicatory methods are complemented by qualitative approaches and methods which emphasize understanding, meanings and symbols.